The effect of customer perceived value on the repurchase decision in the clothing stores - Ashqui Cuvi, Ginger; Bermúdez Gallegos, Christian (Revista Universidad de Guayaquil, 2019)
Perceived value is a concept of growing interest among academics and Marketing professionalssinceit generatessustainable competitive advantage due to its direct relationship with customersatisfactionand loyalty and is considered a reliable predictor of consumer buy-back readiness. The literaturedemands greater attention to this variable in developing countries. The authors summarize fivecomponents such as quality, price, hedonism, ethics, and health. The purpose of this study is toevaluate the components of perceived value that influence the customer's repurchase decision incommercial clothing stores. These were validated through a quantitative approach with a nonexperimental design, with a descriptive scope of the perceived value and correlation with therepurchase decision. The resultsshow that the five components are statistically significant and that ahigher perceived value of the customer, a greater decision to repurchase.
Keywords: perceived value; repurchase decision; clothes store